2017
DOI: 10.1186/s13550-017-0276-1
|View full text |Cite
|
Sign up to set email alerts
|

I-123 iomazenil single photon emission computed tomography for detecting loss of neuronal integrity in patients with traumatic brain injury

Abstract: BackgroundTraumatic brain injury (TBI) causes brain dysfunction in many patients. Using C-11 flumazenil (FMZ) positron emission tomography (PET), we have detected and reported the loss of neuronal integrity, leading to brain dysfunction in TBI patients. Similarly to FMZ PET, I-123 iomazenil (IMZ) single photon emission computed tomography (SPECT) is widely used to determine the distribution of the benzodiazepine receptor (BZR) in the brain cortex. The purpose of this study is to examine whether IMZ SPECT is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(31 reference statements)
2
11
0
Order By: Relevance
“…The observations of focal reductions in BP ND within the frontal lobes, anterior cingulate gyrus, and the thalamus following TBI, are consistent with prior cross-sectional [ 11 C]FMZ studies. 18 , 30 , 55–57 Similarly, our findings of inter-individual variability in the BP ND are consistent with previous reports. 18 , 30 , 55 The notable differences between our study and these previous reports are as follows.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observations of focal reductions in BP ND within the frontal lobes, anterior cingulate gyrus, and the thalamus following TBI, are consistent with prior cross-sectional [ 11 C]FMZ studies. 18 , 30 , 55–57 Similarly, our findings of inter-individual variability in the BP ND are consistent with previous reports. 18 , 30 , 55 The notable differences between our study and these previous reports are as follows.…”
Section: Discussionsupporting
confidence: 93%
“… 18 , 30 , 55–57 Similarly, our findings of inter-individual variability in the BP ND are consistent with previous reports. 18 , 30 , 55 The notable differences between our study and these previous reports are as follows. Our sample spans a fuller range of TBI injury severity from complicated mild to severe compared to previous studies, 18 and patients in our study were not selected a priori by degree of cognitive impairment or cortical damage.…”
Section: Discussionsupporting
confidence: 93%
“…9) A previous study showed that post-CEA hyperperfusion was significantly associated with postoperative hemispheric reduction of BRBP: ≥80% of the pixels with reduced BRBP also exhibited hyperperfusion. 10) Another study indicated that iomazenil SPECT is useful for evaluating loss of neuronal integrity in patients with traumatic brain injury without brain MRI abnormalities, 11) as MRI cannot always demonstrate selective neuronal loss. 7,[10][11][12][13] The above findings and our data indicate that CH after endovascular reperfusion therapy results in postoperative cortical neural damage, even in a region where MRI abnormalities were not found.…”
Section: Discussionmentioning
confidence: 99%
“…10) Another study indicated that iomazenil SPECT is useful for evaluating loss of neuronal integrity in patients with traumatic brain injury without brain MRI abnormalities, 11) as MRI cannot always demonstrate selective neuronal loss. 7,[10][11][12][13] The above findings and our data indicate that CH after endovascular reperfusion therapy results in postoperative cortical neural damage, even in a region where MRI abnormalities were not found. 4,5,7,10,11) However, cortical neural loss, and thus reduced BRBP on later I-123 iomazenil SPECT imaging, may have occurred secondary to hypoperfusion before reperfusion therapy if the hypoperfusion was significant enough to damage the cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation